Studies on Giant and Colossal Magnetoresistance of Alloy and Ceramic Prepared by RF Magnetron Sputtering and Pulsed Laser Ablation Techniques - Lim, Kean Pah (2002)
Magnetic thin films based on the giant magnetoresistance (GMR) and colossal magnetoresistance (CMR) effects are currently being used as head sensor in the magnetic data storage technology. With the technological revolution in the magnetic recording world of last decades, a need of better and more sensitive magnetoresistance material arises for head sensing. In the first part of this work, a series of Ag-Fe-Co granular films with different composition and thickness had been fabricated onto microscope glass slides using RF magnetron sputtering system. The crystalline analysis show that the as-deposited films consist of <111> and <200> silver texture. Negative GMR values have been obtained and no tendency to saturate at any temperature has been observed. The experimental results show that the GMR value is governed by the composition, microstructure, thickness and temperature. Under an optimum condition, formation of the right shape and size of magnetic cluster in the matrix will cause rapid increase of the GMR value.